Librarians as Guiding Lights in the Digital Darkness: A Systematic Review of Libraries’ Provision of Digital Literacy Services - Mensah Danquah, Monica; Ato Yankson, Alfred; Bajamchana Bugase, Elvis; Yirenkyi Nyarko, Christian (Ghana Library Journal, 2026)
In an ever-evolving technological world, digital literacy has become a critical skill for navigating information ecosystems, protecting privacy online, and full and active participation in civic and economic life. This systematic review explores the evolving role of librarians and libraries as key providers of digital literacy services, viewing them as ‘guiding lights’ in tackling the challenges posed by the digital divide and misinformation. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were adopted for the study. A total of 13 electronic databases were used to make a comprehensive search between the years 2004 and 2024. The databases EBSCO Host, Scopus, Web of Science, Emerald, LISTA, LISA, Elsevier, Google Scholar, ProQuest, Taylor & Francis, Springer Link, IEEE Xplore, and Wiley Inter-Science were chosen based on their focus on digital literacy research. A total of 259 papers were included in the review. Seven themes were developed from the review of the included studies. The themes include: digital inclusion initiatives, digital literacy training, e-resources support, virtual reference services, digital collection, challenges, and prospects. Under each major theme, sub-sub-themes were included to fully capture the nuances of the theme. The review concludes with recommendations for library professionals, policy makers, and educators to strengthen collaborative efforts and digitally inclusive strategies to combat the digital divide. The study also advocates for continual investment in librarians and libraries as stewards of equitable access to 21st-century digital skills.